INTEGRASI MODEL STRUKTUR AUTODESK REVIT GEDUNG RUMAH SAKIT MITRA KELUARGA DENGAN PENJADWALAN MICROSOFT PROJECT MENGGUNAKAN AUTODESK NAVISWORK - Habib Ilmi Izzul Haq Zen (Jurnal Vokasi Teknik Sipil, 2024)
The construction field is growing rapidly. The First BIM article in Indonesia was published in 2013, and the first implementation was in 2012. BIM adoption in Indonesia lags behind developed countries (already using BIM since 2000). One of the BIM software is Autodesk Revit & Autodesk Naviswork. There is a lot of software about BIM, including Autodesk Revit & Autodesk Naviswork. The purpose of this research is to explain how to integrate the structural model of Mitra Keluarga Sidoarjo Hospital Building using The Autodesk Revit application with Microsoft Project scheduling using Autodesk Naviswork. The research method used to integrate is by using Autodesk Naviswork software. The results of the integration of the Autodesk Revit model with Microsoft Project scheduling using Autodesk Naviswork are obtained through 4 steps, namely opening the Revit file, importing MS project files, synchronization, and visualization. The Bar Chart used in the project has the advantage of being easy to create and understand. However, it also has disadvantages in terms of little information that makes it difficult to accurately track project progress. On the other hand, Naviswork BIM has the advantage of loaded information, namely visualization of project progress over time. However, it has shortcomings in terms of dependency relationships and critical paths are not visible in scheduling.